Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.7554/elife.03663
|View full text |Cite
|
Sign up to set email alerts
|

Coding of stimulus strength via analog calcium signals in Purkinje cell dendrites of awake mice

Abstract: The climbing fiber input to Purkinje cells acts as a teaching signal by triggering a massive influx of dendritic calcium that marks the occurrence of instructive stimuli during cerebellar learning. Here, we challenge the view that these calcium spikes are all-or-none and only signal whether the instructive stimulus has occurred, without providing parametric information about its features. We imaged ensembles of Purkinje cell dendrites in awake mice and measured their calcium responses to periocular airpuffs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
80
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 93 publications
15
80
0
Order By: Relevance
“…1a), an optically accessible region that, although not previously included among known regions necessary for the production of blinks 2123 , receives excitation that drives movements of nearby trunk and neck regions (Supplementary Fig. 4) and is likely to be engaged during eyeblink conditioning because it receives climbing fiber inputs triggered by the periorbital airpuff US 24,25 . Indeed, in separate nonimaging experiments with five mice that were trained to a high fraction of conditional responses (CR rate > 70%), we found that injection of muscimol in the same region of cerebellar cortex led to a reversible reduction in CR probability and amplitude (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1a), an optically accessible region that, although not previously included among known regions necessary for the production of blinks 2123 , receives excitation that drives movements of nearby trunk and neck regions (Supplementary Fig. 4) and is likely to be engaged during eyeblink conditioning because it receives climbing fiber inputs triggered by the periorbital airpuff US 24,25 . Indeed, in separate nonimaging experiments with five mice that were trained to a high fraction of conditional responses (CR rate > 70%), we found that injection of muscimol in the same region of cerebellar cortex led to a reversible reduction in CR probability and amplitude (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Graded climbing‐fibre induced calcium signals have also been observed in Purkinje cell dendrites in response to eye‐blink conditioning (Najafi et al . ), which may have implications for short‐ and long‐term plasticity. Indeed, behavioural studies have also shown that, during learning of smooth pursuit eye movements, simple spike activity undergoes trial‐by‐trial depression that is related to the duration of complex spikes (Yang & Lisberger, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in reaching tasks, complex spike error signals occur in a small fraction of trials and are evident only after extensive averaging [61, 81]. Graded changes in intracellular Ca ++ as well the distribution of response latencies in Purkinje cell dendrites to sensory events provide possible mechanisms for encoding more than binary information in the complex spike discharge [95, 96]. Also, mitigation of the bandwidth problem has been proposed based on the synchrony of the complex spike discharge at the population level.…”
Section: Potential Issues With Error Encoding By Complex Spikesmentioning
confidence: 99%